THE REFLECTION OF THE PERFECT HUMAN IDEAL THROUGH LITERARY CHARACTERS - Saidova Madinabonu Abduhakim qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
This article explores how the concept of the komil inson (the perfect or morally complete human being) is expressed through literary characters in classical and modern Uzbek literature. Literary heroes often serve as symbolic embodiments of ethical, philosophical, and national ideals. By analyzing selected works, the paper reveals how writers have used character development, internal struggles, and moral choices to represent the evolving image of the ideal human being. The study highlights the educational and spiritual functions of such representations, showing how they influence readers’ understanding of virtue, responsibility, and personal growth. Ultimately, the article demonstrates that literary portrayals of the komil inson serve not only as artistic achievements but also as tools of moral instruction and cultural identity formation.